Kualitas Kedewasaan Rohani serta Implementasinya bagi Jemaat di Abad ke 21: Kajian 2 Petrus 1:3-11 - Baskoro, Paulus Kunto; Hutapea, Orlando (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: Spiritual maturity is an important part of a believer's spiritual life. There are quite a few Christians who have been going to church for a long time but their spiritual condition is still childish, and there are even quite a few church administrators or church servants who, even though they are actively involved in the church, are still often disappointed and hurt. A healthy spiritual life must also experience healthy growth. Spiritual maturity should be an important point since a person experiences repentance and new birth. So that you become a Christian who has the maximum quality of spiritual maturity. This will be studied based on 2 Peter 1:3-11. This research uses descriptive qualitative methods. The aim of this research is First, to find the principles of the quality of spiritual maturity in 2 Peter 1:3-11. Second, the principles of the quality of spiritual maturity can be implemented in the lives of believers today. Third, the quality of maturity of believers grows rapidly and becomes an important part of the process of spiritual life. So, everything experienced by every believer can have a greater impact on personal life and God's church, so that the character of Christ becomes real.Abstrak: Kedewasaan rohani menjadi bagian penting dalam kehidupan spiritual orang percaya. Tidak sedikit orang Kristen, yang sudah lama ke gereja tetapi keadaan rohaninya masih kekanak-kanakan bahkan tidak sedikit pengurus gereja atau pelayan gereja yang meskipun terlibat aktif di dalam gereja namun masih sering kecewa dan sakit hati. Kehidupan rohani yang sehat haruslah mengalami pertumbuhan yang sehat pula. Kedewasaan rohani hendaknya menjadi point penting sejak seseorang mengalami pertobatan dan kelahiran baru. Sehingga menjadi orang Kristen yang memiliki kualitas kedewasaan rohani yang maksimal. Hal ini akan dikaji berdasarkan 2 Petrus 1:3-11. Penelitian ini menggunakan metode kualitatif deskriptif. Tujuan dari penelitian ini adalah Pertama, menemukan prinsip-prinsip kualitas kedewasaan rohani dalam 2 Petrus 1:3-11. Kedua, prinsip-prinsip kualitas kedewasaan rohani dapat diimplementasikan dalam kehidupan orang percaya masa kini. Ketiga, kualitas kedewasaan orang percaya menjadi bertumbuh pesat dan menjadi bagian penting dalam proses kehidupan rohani. Jadi dari semua dialami oleh setiap orang percaya dapat lebih berdampak bagi kehidupan secara pribadi dan gereja Tuhan, sehingga karakter Kristus menjadi nyata.